Blood Pressure Levels and Risks of Dementia: a Nationwide Study of 4.5 Million People. Issue 1 (15th November 2021) - Lee, Chan Joo; Lee, Ji-Yeon; Han, Kyungdo; Kim, Da Hye; Cho, Hanna; Kim, Kwang Joon; Kang, Eun Seok; Cha, Bong-Soo; Lee, Yong-ho; Park, Sungha
Abstract : Supplemental Digital Content is available in the text. Abstract : There are inconsistent results on the impacts of controlling blood pressure (BP) on the risk of dementia. We investigated the association between BP and risk of dementia subtypes by antihypertensive treatment and comorbidities. Using the Korean National Health Insurance Service-Health Screening Database from 2009 to 2012, a total of 4 522 447 adults aged 60+ years without a history of dementia were analyzed and followed up for a mean of 5.4 years. Individuals were classified according to their baseline systolic BP (SBP) and diastolic BP; SBP 130 to <140 mm Hg and diastolic BP 80 to <90 mm Hg were used as reference groups. The risk of overall dementia and probable Alzheimer disease was significantly higher in the SBP≥160 and lower SBP groups. These U-shaped associations were consistent regardless of antihypertensive use or comorbidities. The risk of probable vascular dementia (VaD) was not higher among lower SBP groups and increased gradually as SBP increased. Although there was a linear association between SBP and the risk of probable VaD in individuals not taking antihypertensives or without comorbidities, there was a U-shaped association in individuals taking antihypertensives or with comorbidities. Patterns of association between diastolic BP and risk of probable Alzheimer disease or probable VaD were similar to those with SBP, except for the risk of probable VaD in individuals taking antihypertensives. In conclusion, risks of probable Alzheimer disease and probable VaD were different among lower BP groups. Although the risk of dementia appears higher in people with lower BP receiving antihypertensives, this finding may be affected by comorbidities.